The function of the Notary / PPAT In filing process Acquisition of Land Rights To Interests Investment in Regional Autonomy Era Based on Act No. 25 of 2007 concerning Foreign Investment - Wahyuni Wahyuni; Umar Ma’ruf (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this study are to: 1) To be able to know and analyze about the function of Notary / PPAT in Appeals Process Acquisition of Land Rights Under the Foreign Investment Regulations. 2.) To be able to know and analyze the Protection of Investor Interests Investing in the Era of Regional Autonomy Under the Foreign Investment Law. The method shows the procedure and process of a study undertaken to achieve an objective results. Method of normative juridical approach specifications in this research is descriptive analysis, the data collection method, literature (study document), with critical analysis and finding the problems and legal issues that will be examined and gather all the information related to the problems studied.The results of this study concluded Function Notary / PPAT in the filing process of acquiring land rights based on foreign investment regulations number 25 in 2007. The function of Notaries easier for the public to take legal actions both Indonesian citizens or citizens of foreign countries who participate in investing in Indonesia , The Indonesian government also needs to prepare for national law and the law of international relations to establish it. Government to maintain legal certainty for foreign investors without discrimination by being able to compete with domestic investors. Protection of the interests of investors in investing in regional autonomy based on legislation.Keywords: Function of Notaries; Investments; Autonomy; Foreign Investment.